Shortage of local general workers in Malaysia construction industry / Muhammad Hafiz Anuar and Khalida Mohd Sukur - Anuar, Muhammad Hafiz; Mohd Sukur, Khalida (2018)
There are many challenges faced by the Malaysian Construction industry. Local labours shortage is a major challenge compared to the other challenges in the industry. Malaysian construction industry has a problem in the ability to get the source of labours and has to depend on foreign workers to meet the high demand of skilled workers due to rapid development. The aim of this research is to look more closely the influencing factors that contribute to the shortage of the local labours as well as to discuss how these challenges can be managed. Thus, the objectives of this research are to identify the causes of shortage of local general workers and to identify the techniques to attract the local workers to involve in the construction industry. The assessment was conducted via questionnaire to 28 respondents from industry key players at Klang, Selangor. The finding of this research is to give benefits to the local people, especially on job opportunities in construction industry towards optimal performance.